Degradation of Executorial Rights and Execution Parate Institutions on Fiduciary Security After the Decision of the Konstitution Court Number 18/Puu-Xvii/2019 - Yeni Triana; Yelia Nathassa Winstar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Constitutional Court decision Number 18/PUU-XVII/2019 degrades the existence of executorial rights and execution parate institutions in the UUJF. Melements of the substance of the law in rangka this execution resulted in the purpose of the law can not be met. PeneThis research is a normative juridical research that will answer several questions. First, what is the essence of the position of eksekutorial rights, execution parate, promise injury clause in fiduciary security rules. Second, how the juridical analysis of the Constitutional konstitusi tersebutCourt decision. This study produced several results, first the decision of the Constitutional Court contradicts the essence of the existence of executorial rights and the institution of Parate execution. executorial rights and execution parate institutions arise from the existence of special guarantees granted privileges through executorial rights institutions and execution parate institutions. The article of promise injury in the main agreement essentially serves as clause naturalia. The naturalia clause means that althoughthis clause is not expressly stated, theinjury clause promises to remain. The nature pelaksanaanof execution is because there is no voluntary act of implementing a decision that has permanent legal force. Thus, establishing the validity of the executorial right when there is a voluntary surrender is contrary to the nature of the execution itself. Second, in making a decision, the judge should put forward the principle of legal mind, namely legal certainty, justice and usefulness. In the Constitutional Court ruling amar judge's decision does not reflect the certainty, justice and kemanfaatn